Management of Congenital Long-QT Syndrome: Commentary From the Experts. (July 2021) - Kaufman, Elizabeth S.; Eckhardt, Lee L.; Ackerman, Michael J.; Aziz, Peter F.; Behr, Elijah R.; Cerrone, Marina; Chung, Mina K.; Cutler, Michael J.; Etheridge, Susan P.; Krahn, Andrew D.; Lubitz, Steven A.; Perez, Marco V.; et al.
Abstract : While published guidelines are useful in the care of patients with long-QT syndrome, it can be difficult to decide how to apply the guidelines to individual patients, particularly those with intermediate risk. We explored the diversity of opinion among 24 clinicians with expertise in long-QT syndrome. Experts from various regions and institutions were presented with 4 challenging clinical scenarios and asked to provide commentary emphasizing why they would make their treatment recommendations. All 24 authors were asked to vote on case-specific questions so as to demonstrate the degree of consensus or divergence of opinion. Of 24 authors, 23 voted and 1 abstained. Details of voting results with commentary are presented. There was consensus on several key points, particularly on the importance of the diagnostic evaluation and of β-blocker use. There was diversity of opinion about the appropriate use of other therapeutic measures in intermediate-risk individuals. Significant gaps in knowledge were identified. Abstract : Supplemental Digital Content is available in the text.